2010
DOI: 10.1017/s1751731110001308
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary n-3 fatty acids on characteristics and lipid composition of ovine sperm

Abstract: The fatty acid composition of sperm affects the fertilization rate. The objective was to investigate the effects of dietary fish oil (as a source of n-3 fatty acids) on semen quality and sperm fatty acid composition in sheep. Eight Zandi fat-tailed rams were randomly allocated into two groups and fed either a control diet or a diet supplemented with fish oil. Both diets were isocaloric and isonitrogenous and were fed for 13 weeks, starting in the middle of the breeding season. Semen samples were collected week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
46
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 30 publications
13
46
0
3
Order By: Relevance
“…There have been several studies with regards to the supplementation of fish oil into the rooster (10), boar (12) goat (29), sheep (30) and turkey (31) diet. The results revealed that the diet supplemented with fish oil led to an increase in sperm progressive motility.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies with regards to the supplementation of fish oil into the rooster (10), boar (12) goat (29), sheep (30) and turkey (31) diet. The results revealed that the diet supplemented with fish oil led to an increase in sperm progressive motility.…”
Section: Discussionmentioning
confidence: 99%
“…In most mammals, fatty acid composition of their spermatozoa is characterized by very high proportions of n-3 PUFAs (Kelso et al, 1997;Samadian et al, 2010). Docosahexaenoic (DHA) has been reported to be the predominant PUFAs within the sperm plasma membrane (Maldjian et al, 2005), but during the cryopreservation process, the level of PUFAs decreases significantly because of lipid peroxidation (Cerolini et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have assessed the effect of fish oil addition on semen quality parameters in domestic animals. They have reported that fish oil caused increments in sperm motility and reductions in abnormal sperm in boars [9] , improved fertility in turkeys [10] as well as increased total of sperm count in rams [11] . On the other hand, the addition of fish oil as a source of omega-3 fatty acids to diet of boars has been demonstrated to possess no significant improvement effect on the quality of frozen-thawed sperm [12] .…”
Section: Introductionmentioning
confidence: 99%